EFFECT OF AMLODIPINE ON CIRCADIAN RHYTHM OF BLOOD PRESSURE IN HYPERTENSIVE FEMALE PATIENTS WITH DIFFERENT PSYCHO-EMOTIONAL BACKGROUND - V. R. Veber; M. P. Rubanova; S. V. Zhmailova; P. M. Gubskaya; A. I. Vinogradov (Столичная издательская компания, 2017)
Aim. To study the changes in indicators of 24-hours blood pressure (BP) monitoring during the antihypertensive treatment with amlodipine in hypertensive women with normal psycho-emotional status or with subclinical depression.Material and methods.  29 women with stage 2 hypertension were divided into 2 groups. 24-hours BP monitoring was performed in Group 1 (n=15; mean age 45.4±1.7 years; with normal psycho-emotional status) and Group 2 (n=14; mean age 46.7±1.3 years; with subclinical depression) at base- line and after 1 month of amlodipine treatment. We analyzed the dynamics of the following indicators: time index (VI), load measurement index (AI) of increased and reduced systolic (SBP) and diastolic (DBP) BP, reflecting the influence of hypertension and hypotension on the target organs.Results.  BP variability during the day was higher in group 2 than in group 1. Increase in load by increased DBP at night was found during amlodipine therapy in both groups: from 34.5±8.7 to 84.8±14.8 (p=0.006) in the Group 1 and from 38.5±10.2 to 95.3±14.7 (p=0.004) in the Group 2. Be- sides increase in load by reduced SBP during a day was also observed in both groups: from 9.1±3.2 to 45.4±12.8 (p=0.0039) in the Group 1 and from 0.5±0.06 to 53.8±13.1 (p=0.0016) in the Group 2. DBP variability at night increased from 7.5±0.8 to 10.3±0.8 (p=0.011) in the Group 1 and from 8.5±0.4 to 9.7±0.8 (p=0.083) in the Group 2. Increase in severity of subclinical depression according to HADS was demonstrated in Group 2 after one month of treatment with amlodipine.Conclusion.  The use of amlodipine requires regular control of 24-hours BP monitoring indices and assessment of mental and emotional status dynamics